Bullying em uma escola pública no município de Piraquê-TO: autopercepção e sofrimento. - Oliveira, Maria da Assunção Nascimento de (Universidade Federal do Tocantins, 2022)
Violence has become common within the school environment, and due to the observation of excessive aggressive acts that have appeared in the media in recent years, the interest and motivation to explore the bullying theme in the school space has been broken. Given the pretension of knowing possible solutions and given the importance of the subject, the objective is to verify the occurrence of bullying, its victims and perpetrators and the knowledge of elementary and high school students of a state school in the city of Piraquê. To this end, we present an approach to bullying and its conflicts in society and school, as well as the roles of school and family. It also presents reports of bullying research in Brazil, at school and in society. The work had as a method a quantitative research in a public school of the city of Piraquê-To, using a questionnaire with 20 questions in order to obtain results of the incidence of bullying cases in the school. The research was applied in four classes, among them were 8th and 9th grade of elementary school, 1st and 3rd year of high school. Therefore, it is concluded with the research that there is a high incidence of bullying in the school studied, and part of the aggressors are male, and the situations of aggression occur in supervised environments such as the classroom and the school yard. Such results demonstrate that the school needs to be organized in another way in order to reduce the cases of escalating violence. The participation of school, students, parents and the community in the fight to reduce bullying is crucial.